2012
DOI: 10.1681/asn.2011090920
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Autoantibodies to hLAMP-2 in Anti–Neutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: The involvement of autoantibodies to human lysosome-associated membrane protein-2 (hLAMP-2) in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is controversial because of the absence of confirmatory data subsequent to the initial reports of their high prevalence in this disease. We characterized three assays for anti-hLAMP-2 antibodies: ELISA and Western blotting assays using unglycosylated recombinant hLAMP-2 expressed in Escherichia coli, and an indirect immunofluorescence assay using stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
93
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 32 publications
4
93
2
4
Order By: Relevance
“…Although this finding fails to achieve statistical significance, it provides a hint that population differences may contribute to the discordant findings. However, even in this subset, the prevalence of anti-LAMP-2 remains substantially lower than the prevalence reported in the work by Kain et al, 9 suggesting that additional factors are also involved.…”
contrasting
confidence: 72%
See 4 more Smart Citations
“…Although this finding fails to achieve statistical significance, it provides a hint that population differences may contribute to the discordant findings. However, even in this subset, the prevalence of anti-LAMP-2 remains substantially lower than the prevalence reported in the work by Kain et al, 9 suggesting that additional factors are also involved.…”
contrasting
confidence: 72%
“…A consistent feature of the studies by Kain et al 6,9 has been that the highest anti-LAMP-2 antibody prevalence is in patients presenting with an untreated, active glomerulonephritis. Moreover, they found that anti-LAMP-2 titers are remarkably sensitive to disease activity and/or immunosuppression to the extent that, in their current report, Kain et al…”
supporting
confidence: 58%
See 3 more Smart Citations